Preparation method and application of coated nano modifying and flooding agent

By adding a terminator to the polymerization process of core-shell nano-driver control agents to control their molecular weight and molecular weight distribution, the problem of poor stability of core-shell nano-driver control agents is solved, and stable preparation of coated nano-driver control agents is achieved. Application in low-permeability oil fields.

CN119505100APending Publication Date: 2025-02-25NINGBO FENGCHENG NANOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411487107.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing core-shell nano-driver has poor stability during the production process, resulting in unstable viscosity and excessive particle size, which affects its application effect in low-permeability oil fields.

Method used

By regulating the core and shell polymerization process, a terminator is added to control the molecular weight and molecular weight distribution of the polymer, ensuring that the viscosity and particle size of the product are within a suitable range, forming a stable coated nano-driver.

Benefits of technology

The stable performance of the coated nano-driver is achieved, with a particle size distribution of 50-150nm and a viscosity of 2000-5000mPa·S. It is suitable for the mineralized water quality and formation temperature requirements of low-permeability oil fields, and simplifies the preparation process, which is suitable for large-scale Large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505100A_ABST
    Figure CN119505100A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a coated nano profile control and flooding agent.The preparation method comprises the following steps that S1, a styrene compound and an olefine acid ester compound are added into an emulsifier solution to be mixed to obtain a core emulsion, a cross-linking agent is added into the core emulsion to be mixed and deoxygenized, an initiator I is added into the emulsion, a reaction I is carried out, and a reaction liquid is obtained; an oil-soluble inner core is obtained; and S2, adding the oil-soluble core into a water-soluble monomer solution, removing oxygen, adding an initiator II, reacting II, and adding a terminator solution to obtain the coated nano profile control and flooding agent. According to the coated nano profile control and flooding agent provided by the invention, the chain terminator is added, so that the stability of the coated nano profile control and flooding agent is relatively good. The preparation method of the coated nano modifying and flooding agent is simple, convenient to operate and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of a coated nano-displacement agent, belonging to the technical field of deep displacement. Background Art

[0002] my country has rich reserves of low-permeability and ultra-low-permeability oil and gas resources, among which low-permeability reservoirs with developed fractures account for a very large proportion. During the water injection development of low-permeability fractured reservoirs, due to the long-term scouring of injected water, the reservoir properties and pore structure are quite different from the original reservoir characteristics, which has a great impact on the subsequent water injection development and oil production. The development situation of low-permeability fractured reservoirs is severe. The main reasons for the low development efficiency are the strong heterogeneity and high degree of fracture development. The heterogeneity of the reservoir is aggravated, resulting in ineffective water injection circulation and reduced oil recovery efficiency. The deep flooding technology of water injection wells can effectively improve the water flooding effect of heterogeneous reservoirs and is a key technology to improve the water flooding effect in the later stage of development.

[0003] Deep flooding technology has become one of the main means for secondary development of high-water-content oil fields in my country, improving the water flooding development effect of oil reservoirs and increasing recovery. This technology mainly injects flooding agents with good mobility into the formation through water injection wells. As the flooding agents migrate to the deep formation, they seal the high permeability layer, balance the water absorption profile, cause the deep liquid flow to turn, and drive out the residual oil in the formation, thereby increasing the recovery of crude oil.

[0004] The core-shell material has better stability due to its core-shell structure, which provides the material with strong pressure resistance and anti-fracture function, so it can play a role in deep displacement in harsher formation environments. How to develop new core-shell materials to further improve crude oil recovery is worth studying.

[0005] Commonly used deep displacement agents at home and abroad can be divided into: polymer gels, polymer jellies, pre-crosslinked expanded particles, and polymer microspheres. Patent CN116023593A discloses a nano displacement material and its preparation method and application. The invention synthesizes nano core-shell materials through a one-step or multi-step polymerization method, and uses molecular design theory to regulate the molecular structure and molecular weight distribution of the inner core oil-soluble nanomaterial to design an inner core material of a certain size; using a water-soluble monomer as the outer shell, this shell has good temperature and salt resistance, and has a protective and supporting effect on the inner core. In the process of the water-soluble shell material carrying the inner core to the deep reservoir, the water-soluble shell material releases the oil-soluble inner core material due to factors such as formation shear, adsorption or swelling; through the migration of the oil-soluble inner core in the reservoir, it blocks water when it encounters water and washes oil when it encounters oil, thereby playing the role of intelligent displacement.

[0006] In the early stage of R&D and process production, it was found that the core-shell product was not stable enough due to the influence of reaction monomers, reaction conditions and other factors. For example, when the reaction temperature is too high, the free radical collisions generated in the reaction become uncontrolled, resulting in the rate of chain reaction out of control, thus triggering the "implosion" phenomenon, thus increasing the viscosity of the core-shell product, reducing the conversion rate, and increasing the particle size of the reaction product; if the initiation temperature is low, then the system will produce fewer active free radicals, and the collision frequency between molecules will be low, so the reaction conversion rate will be low and the particle size will be larger.

[0007] In addition, during the production process, due to the large output of one-time synthesis, the heating temperatures of various parts of the emulsion in the reaction container are inconsistent, and the extent of the reaction is usually determined by viscosity changes. It is necessary to continuously take samples for viscosity testing during the synthesis process, resulting in low production efficiency. In addition, if the viscosity suddenly changes sharply during the production process, it is difficult to interrupt the emulsion polymerization process by stopping the reaction or rapidly cooling the temperature, resulting in poor stability of the synthetic product, and sometimes core-shell products with higher or lower viscosity will appear. Summary of the invention

[0008] In order to solve the problem of poor stability of core-shell products in the above-mentioned actual production process, the present application regulates the core and shell polymerization processes, and the product is still a coated structure in which a water-soluble material encapsulates an oil-soluble material, and a certain amount of terminator is added in the shell emulsion reaction stage. The chain terminator can act as a regulator to participate in the free radical polymerization process of acrylamide, and realize chain transfer and control by reacting with polymerization active free radicals, thereby regulating the molecular weight and molecular weight distribution of the polymer, so as to achieve the effect of controlling the viscosity and reaction degree of the product, so that the product performance is stable and the synthesis process is controllable.

[0009] Compared with the prior art, the coated nano-type flooding agent provided in the present application has a particle size distribution of 50 to 150 nm, a viscosity of 2000 to 5000 mPa·S, remains a milky white flowable liquid without stratification after long-term storage, is easily soluble and completely dispersed in water, and the diluted liquid is clear and transparent without flocs or precipitation, and can adapt to the mineralized water quality and formation temperature requirements of low-permeability oilfield formations; and the preparation method of the coated nano-type flooding agent is simple, easy to operate, and suitable for large-scale production.

[0010] According to one aspect of the present application, a method for preparing a coated nano-propeller is provided, the method comprising the following steps:

[0011] S1: adding a styrene compound and an olefinic acid ester compound to an emulsifier solution and mixing to obtain a core emulsion, adding a crosslinking agent to the core emulsion and mixing, deoxygenating, and then adding an initiator I to the emulsion, reacting I, and obtaining an oil-soluble core;

[0012] S2: adding the oil-soluble core into the water-soluble monomer solution, deoxygenating, then adding initiator II, reacting II, adding terminator solution, and obtaining a coated nano-adjusting agent.

[0013] Optionally, in step S2, the terminator in the terminator solution is selected from at least one of thiourea, sodium dimethyldithiocarbamate, sodium polysulfide, and sodium nitrite.

[0014] Optionally, the concentration of the terminator solution is 1% to 5%, and the concentration of the terminator solution is measured by mass.

[0015] Optionally, the concentration of the terminator solution is independently selected from any value of 1%, 2%, 3%, 4%, 5%, or a range between any two of the above.

[0016] Optionally, the mass proportion of the terminator solution in the coated nano-propeller is 0.5% to 1.5%.

[0017] Optionally, the mass proportion of the terminator solution in the coated nano-propeller is independently selected from any value among 0.5%, 0.8%, 1%, 1.2%, 1.5%, or a range between any two of the above.

[0018] Optionally, in step S1, the emulsifier in the emulsifier solution is selected from at least one of Tween 80, Span 60, NP-10, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0019] Optionally, the mass proportion of the emulsifier in the emulsifier solution is 10-20%.

[0020] Optionally, the mass proportion of the emulsifier in the emulsifier solution is independently selected from any value of 10%, 12%, 14%, 15%, 16%, 18%, 20% or a range between any two of the above.

[0021] Optionally, the styrene compound is selected from styrene and / or methylstyrene.

[0022] Optionally, the olefinic acid ester compound is selected from octadecyl acrylate and / or octadecyl methacrylate.

[0023] Optionally, the mass ratio of the styrene compound to the olefinic acid ester compound is 9:1 to 1:1.

[0024] Optionally, the mass ratio of the styrene compound to the olefinic acid ester compound is independently selected from any value of 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1 or a range between any two of the above values.

[0025] Optionally, the mass proportion of the styrene compound and the acrylate compound in the inner core emulsion is 10-20%.

[0026] Optionally, the mass proportion of the styrene compound and the olefinic acid ester compound in the inner core emulsion is independently selected from any value of 10%, 12%, 14%, 15%, 18%, 20% or a range between any two of the above.

[0027] Optionally, in step S1, the cross-linking agent is NN methylenebisacrylamide.

[0028] Optionally, the mass proportion of the cross-linking agent in the inner core emulsion is 0.01-0.05%.

[0029] Optionally, the mass proportion of the crosslinking agent in the inner core emulsion is independently selected from any value among 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or a range between any two of the above.

[0030] Optionally, the initiator I is selected from at least one of azobisisobutyronitrile, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0031] Optionally, the mass proportion of initiator I in the inner core emulsion is 0.05% to 0.1%.

[0032] Optionally, the mass proportion of initiator I in the inner core emulsion is independently selected from any value among 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or a range between any two of the above.

[0033] Optionally, in step S2, the water-soluble monomer in the water-soluble monomer solution is selected from at least one of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, sodium 2-acrylamide-2-methylpropane sulfonate, and acrylic acid.

[0034] Optionally, the mass proportion of the water-soluble monomer in the water-soluble monomer solution is 20-50%.

[0035] Optionally, the pH value of the water-soluble monomer solution is 6-8.

[0036] Optionally, the mass proportion of the water-soluble monomer solution in the coated nano-propeller is 10-15%.

[0037] Optionally, in step S2, the initiator II is selected from at least one of azobisisobutyronitrile, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0038] Optionally, the mass proportion of initiator II in the water-soluble monomer solution is 0.1-0.5%.

[0039] Optionally, in steps S1 and S2, the deoxygenation method is independently selected from nitrogen replacement for 20 to 40 minutes.

[0040] Optionally, the stirring speeds of the reaction I and the reaction II are independently selected from 100 to 300 r / min.

[0041] Optionally, the temperature of reaction I and reaction II is independently selected from 40 to 80° C., and the time of reaction I and reaction II is independently selected from 2 to 6 hours.

[0042] According to another aspect of the present application, a coated nano-type displacement control agent prepared by the above-mentioned preparation method is provided, wherein the particle size of the coated nano-type displacement control agent is 50 to 150 nm.

[0043] Optionally, the viscosity of the coated nano-propeller is 2000-5000 mPa·S.

[0044] According to another aspect of the present application, there is provided a use of the above-mentioned coated nano-displacement agent in a low-permeability oilfield core.

[0045] Optionally, the coated nano-type displacement agent is dissolved in mineralized water and injected into the core, and the mass proportion of the coated nano-type displacement agent in the mineralized water is 0.5% to 1.5%.

[0046] As an optional implementation method, the present application is implemented through the following technical solutions:

[0047] The preparation method of the coated nano-propeller comprises the following steps:

[0048] Step 1: firstly mix deionized water and an emulsifier to obtain an emulsifier solution, then add a styrene compound and an acrylate compound to the emulsifier solution to obtain a core emulsion, add a crosslinking agent to the emulsion, deoxygenate it, heat it, add an initiator, and react for a period of time to obtain an oil-soluble core.

[0049] Step 2: adding a water-soluble monomer solution to the oil-soluble core emulsion, adding an initiator after deoxygenation, and adding a terminator solution after a period of reaction to obtain a coated nano-adjusting agent.

[0050] The beneficial effects of this application include:

[0051] 1) The preparation method of the coated nano-adjusting agent provided in the present application is a core-shell structure in which a water-soluble material encapsulates an oil-soluble material. The emulsifier is first dissolved in water so that the oil-soluble core can form a stable core emulsion in the emulsifier solution. The oil-soluble core is then coated with a water-soluble shell to form a regular core-shell emulsion. The reaction is controllable by adjusting the parameters in the synthesis process and adding a terminator, thereby controlling the product viscosity and the size of the core-shell material.

[0052] 2) The preparation method of the coated nano-type control agent provided in the present application is to first synthesize an oil-soluble core by emulsion polymerization, and then add a water-soluble monomer to form a water-soluble shell. The water-soluble shell covers the oil-soluble core, which protects, supports and disperses the oil-soluble core; so that the coated nano-type control agent has a regular spherical nano-core-shell structure and a small initial particle size of 50-150nm.

[0053] 3) The preparation method of the coated nano-adjusting agent provided in the present application makes the reaction temperature and reaction time controllable by adding a terminator, thereby controlling the viscosity and size of the synthesized product; the preparation method is simple, easy to operate, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a diagram of the initial particle size of the coated nano-propeller in Example 1 of the present application.

[0055] Figure 2 This is the displacement diagram of the coated nano-displacement agent prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0056] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0057] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0058] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0059] Example 1 Preparation of coated nano-adjusting agent

[0060] (1) Weigh 550 g of deionized water, add 100 g of emulsifier (Tween 80), place in a three-necked flask, and stir at 200 r / min and 40°C until completely dissolved.

[0061] (2) Weigh 100 g of a styrene compound (styrene) and 40 g of an acrylate compound (octadecyl acrylate), and stir at 200 r / min and 40° C. until the mixture is completely dissolved.

[0062] (3) Pour the dissolved mixture in step (2) into the mixture in step (1) at once, stir at 200 r / min and 40° C. for 10 min, add 0.12 g of a cross-linking agent (NN methylenebisacrylamide) and 0.7 g of a cross-linking agent (azobisisobutyronitrile), introduce nitrogen for 20 min, then heat to 70° C. and react for 3 h to obtain an oil-soluble core.

[0063] (4) Weigh 34 g of acrylamide and 12 g of sodium 2-acrylamido-2-methylpropane sulfonate and add deionized water to stir and dissolve to obtain 100 g of water-soluble monomer, add the water-soluble monomer to the oil-soluble core, introduce nitrogen for 20 min, then add 10 g of initiator solution (0.4% potassium persulfate aqueous solution), stir at 200 r / min and 80° C. until the core-shell emulsion has a certain viscosity, then add 20 g of terminator solution (1% thiourea aqueous solution) to obtain a coated nano-type control agent with a particle size of 50 nm and a viscosity of 2000 mPa·S.

[0064] Example 2 Preparation of coated nano-adjusting agent

[0065] (1) Weigh 550 g of deionized water, add 100 g of emulsifier (Tween 80), place in a three-necked flask, and stir at 150 r / min and 40°C until completely dissolved.

[0066] (2) Weigh 90 g of a styrene compound (styrene) and 50 g of an acrylate compound (octadecyl acrylate), and stir at 150 r / min and 40° C. until they are completely dissolved.

[0067] (3) Pour the dissolved mixture in step (2) into the mixture in step (1) at once, stir at 200 r / min and 40° C. for 10 min, add 0.14 g of a cross-linking agent (NN methylenebisacrylamide) and 0.7 g of a cross-linking agent (azobisisobutyronitrile), pass nitrogen for 20 min, then heat to 70° C. and react for 3 h to obtain an oil-soluble core.

[0068] (4) Weigh 34 g of acrylamide and 12 g of sodium 2-acrylamido-2-methylpropane sulfonate and add deionized water to stir and dissolve to obtain 100 g of water-soluble monomer, add the water-soluble monomer to the oil-soluble core, introduce nitrogen for 20 min, then add 10 g of initiator solution (0.4% potassium persulfate aqueous solution), stir at 150 r / min and 80° C. until the core-shell emulsion has a certain viscosity, then add 20 g of terminator solution (1% thiourea aqueous solution) to obtain a coated nano-type control agent with a particle size of 100 nm and a viscosity of 3500 mPa·S.

[0069] Example 3 Preparation of coated nano-adjusting agent

[0070] (1) Weigh 500 g of deionized water, add 100 g of emulsifier (Tween 80), place in a three-necked flask, and stir at 150 r / min and 40°C until completely dissolved.

[0071] (2) Weigh 100 g of a styrene compound (styrene) and 40 g of an acrylate compound (octadecyl acrylate), and stir at 200 r / min and 40° C. until the mixture is completely dissolved.

[0072] (3) Pour the dissolved mixture in step (2) into the mixture in step (1) at once, stir at 200 r / min and 40° C. for 10 min, add 0.2 g of a cross-linking agent (NN methylenebisacrylamide) and 0.7 g of a cross-linking agent (azobisisobutyronitrile), pass nitrogen for 30 min, then heat to 70° C. and react for 3 h to obtain an oil-soluble core.

[0073] (4) Weigh 40 g of acrylamide and 20 g of sodium 2-acrylamido-2-methylpropane sulfonate and add deionized water to stir and dissolve to obtain 100 g of water-soluble monomer, add the water-soluble monomer to the oil-soluble core, introduce nitrogen for 30 min, then add 10 g of initiator solution (0.5% potassium persulfate aqueous solution), stir at 200 r / min and 80° C. until the core-shell emulsion has a certain viscosity, then add 20 g of terminator solution (2% thiourea aqueous solution) to obtain a coated nano-type control agent with a particle size of 150 nm and a viscosity of 5000 mPa·S.

[0074] Comparative Example 1

[0075] (1) Weigh 550 g of deionized water, add 100 g of emulsifier (Tween 80), place in a three-necked flask, and stir at 150 r / min and 40°C until completely dissolved.

[0076] (2) Weigh 100 g of a styrene compound (styrene) and 40 g of an acrylate compound (octadecyl acrylate), and stir at 200 r / min and 40° C. until the mixture is completely dissolved.

[0077] (3) Pour the dissolved mixture in step (2) into the mixture in step (1) at once, stir at 200 r / min and 40° C. for 10 min, add 0.14 g of a cross-linking agent (NN methylenebisacrylamide) and 0.7 g of a cross-linking agent (azobisisobutyronitrile), pass nitrogen for 20 min, then heat to 70° C. and react for 3 h to obtain an oil-soluble core.

[0078] (4) Weigh 34 g of acrylamide and 12 g of sodium 2-acrylamido-2-methylpropane sulfonate and add deionized water to stir and dissolve to obtain 100 g of water-soluble monomer, add the water-soluble monomer to the oil-soluble core, introduce nitrogen for 20 min, then add 10 g of initiator solution (0.4% potassium persulfate aqueous solution), stir at 200 r / min and 80° C. for 4 h to obtain a coated nano-propeller with a particle size of 90 nm and a viscosity of 1200 mPa·S.

[0079] Comparative Example 2

[0080] (1) Weigh 550 g of deionized water, add 100 g of emulsifier (Tween 80), place in a three-necked flask, and stir at 150 r / min and 40°C until completely dissolved.

[0081] (2) Weigh 100 g of a styrene compound (styrene) and 40 g of an acrylate compound (octadecyl acrylate), and stir at 200 r / min and 40° C. until the mixture is completely dissolved.

[0082] (3) Pour the dissolved mixture in step (2) into the mixture in step (1) at once, stir at 200 r / min and 40° C. for 10 min, add 0.14 g of a cross-linking agent (NN methylenebisacrylamide) and 0.7 g of a cross-linking agent (azobisisobutyronitrile), pass nitrogen for 20 min, then heat to 70° C. and react for 3 h to obtain an oil-soluble core.

[0083] (4) Weigh 34 g of acrylamide and 12 g of sodium 2-acrylamido-2-methylpropane sulfonate and add deionized water to stir and dissolve to obtain 100 g of water-soluble monomer, add the water-soluble monomer to the oil-soluble core, introduce nitrogen for 20 min, then add 10 g of initiator solution (0.4% potassium persulfate aqueous solution), stir at 200 r / min and 80° C. for 4 h to obtain a coated nano-propeller.

[0084] Test Example 1 Solubility and Particle Size

[0085] Performance tests were performed on samples of Examples 1 to 3 and Comparative Examples 1 to 2.

[0086] Weigh 1.5 g of the coated nano-adjusting agent prepared in Example 1 into a 250 mL beaker, then add 98.5 g of 7000 ppm NaCl mineralized water into the beaker, stir with magnetic stirring at 500 rpm at room temperature until the sample is basically dissolved. Add the CSN-04 dilution into the particle size test sample pool, put the sample pool into the particle size analyzer, test the particle size, and take the average of the particle size for 3 times and record it.

[0087] like Figure 1As shown, the test results: the initial particle size is 88.01nm, and the dilution liquid is stable, without flocs and precipitation.

[0088] Test Example 2 Dilution Stability

[0089] 40-50 g of the coated nano-adjusting agent dilution prepared in Example 1 was transferred into a transparent glass bottle, and the stability was continuously observed at room temperature (25° C.) for 24 hours. The dilution stability evaluation criteria: the dilution was not stratified and there was no large particle precipitation.

[0090] Test results: Under room temperature conditions, the diluted solution did not separate into layers and no large particles precipitated after 24 hours.

[0091] Test Example 3 Determination of Recovery Factor

[0092] (1) Take the dried core and weigh its dry weight. After vacuuming and saturating it with simulated water, weigh its wet weight and calculate the pore volume.

[0093] (2) Water permeability: Inject simulated water at a rate of 0.3 mL / min. After the injection pressure stabilizes, calculate the water permeability of the core.

[0094] (3) Oil saturation: The core was placed in a displacement device and oil was injected at a rate of 0.3 mL / min until the produced fluid contained no water. The produced water volume was recorded and the oil saturation was calculated. The saturated oil volume was recorded as V, aging;

[0095] (4) Water flooding: Inject simulated formation brine at a rate of 0.3 mL / min, and record the liquid production, water production, oil production and pressure at regular intervals. The water flooding equilibrium pressure is P1, and the water flooding oil production is V1;

[0096] (5) Agent flooding: Inject the prepared coated nano-adjustment and flooding agent dilution at a rate of 0.3 mL / min, record the liquid production, water production, oil production and pressure at regular intervals, and record the aging and agent flooding oil production as V2;

[0097] (6) Post-water flooding: Post-water flooding was performed at a rate of 0.3 mL / min. The liquid production, water production, oil production and pressure were recorded at regular intervals. The flooding was completed when the comprehensive water content reached 98%. The post-water flooding equilibrium pressure was P2, and the post-water flooding oil production was recorded as V3.

[0098] (7) Calculation formula for enhanced oil recovery:

[0099] Experimental results:

[0100] Table 1: Plugging performance

[0101]

[0102] Table 2: Oil displacement effect

[0103]

[0104] It can be seen from Table 1 and Table 2 that the coated nano-displacement agents prepared in Examples 1 to 3 are superior to those in Comparative Examples 1 to 2 in terms of plugging performance and enhanced oil recovery.

[0105] like Figure 2 As shown, from Figure 2 It can be seen that the coated nano-type flooding agent of Example 1 increases the pressure more and has a higher plugging rate during the flooding process, indicating that the nano-type flooding agent has excellent plugging and flooding performance.

[0106] Test Example 4 Effect of Terminator Dosage

[0107] The effect of different amounts of terminator on the core-shell emulsion stock solution and dilution solution in the preparation of coated nano-adjusting and displacement agents was studied. The specific situation is shown in Table 3.

[0108] Table 3 Effect of the amount of terminator

[0109]

[0110] From Table 3, it can be seen that when no terminator is added, the core-shell emulsion product may have a low or high viscosity. If the viscosity of the core-shell emulsion is low, the stock solution will be stratified after 24 hours; if the viscosity of the core-shell emulsion is high, it will be insoluble and unusable and have poor injection performance. When the terminator is added, the coated nano-adjusting agent is stable, and the particle size is evenly distributed between 80 and 100 nm.

[0111] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a coated nano-propeller, characterized in that: The preparation method comprises the following steps: S1: adding a styrene compound and an olefinic acid ester compound to an emulsifier solution and mixing to obtain a core emulsion, adding a crosslinking agent to the core emulsion and mixing, deoxygenating, and then adding an initiator I to the emulsion, reacting I, and obtaining an oil-soluble core; S2: adding the oil-soluble core into the water-soluble monomer solution, deoxygenating, then adding initiator II, reacting II, adding terminator solution, and obtaining a coated nano-adjusting agent.

2. The preparation method according to claim 1, characterized in that: In step S2, the terminator in the terminator solution is selected from at least one of thiourea, sodium dimethyldithiocarbamate, sodium polysulfide, and sodium nitrite; Preferably, the concentration of the terminator solution is 1% to 5%, and the concentration of the terminator solution is measured by mass; Preferably, the mass proportion of the terminator solution in the coated nano-propeller is 0.5% to 1.5%.

3. The preparation method according to claim 1, characterized in that: In step S1, the emulsifier in the emulsifier solution is selected from at least one of Tween 80, Span 60, NP-10, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; Preferably, the mass proportion of the emulsifier in the emulsifier solution is 10-20%; Preferably, the styrene compound is selected from styrene and / or methylstyrene; Preferably, the olefinic acid lipid compound is selected from octadecyl acrylate and / or octadecyl methacrylate; Preferably, the mass ratio of the styrene compound to the olefinic acid ester compound is 9:1 to 1:1; Preferably, the mass proportion of the styrene compound and the acrylate compound in the inner core emulsion is 10-20%.

4. The preparation method according to claim 1, characterized in that: In the step S1, the cross-linking agent is NN methylene bisacrylamide; Preferably, the mass proportion of the crosslinking agent in the inner core emulsion is 0.01 to 0.05%; Preferably, the initiator I is selected from at least one of azobisisobutyronitrile, potassium persulfate, sodium persulfate, and ammonium persulfate; Preferably, the mass proportion of initiator I in the inner core emulsion is 0.05% to 0.1%.

5. The preparation method according to claim 1, characterized in that: In the step S2, the water-soluble monomer in the water-soluble monomer solution is selected from at least one of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, sodium 2-acrylamide-2-methylpropane sulfonate, and acrylic acid; Preferably, the mass proportion of the water-soluble monomer in the water-soluble monomer solution is 20-50%; Preferably, the pH value of the water-soluble monomer solution is 6 to 8; Preferably, the mass proportion of the water-soluble monomer solution in the coated nano-propeller is 10-15%.

6. The preparation method according to claim 1, characterized in that: In the step S2, the initiator II is selected from at least one of azobisisobutyronitrile, potassium persulfate, sodium persulfate, and ammonium persulfate; Preferably, the mass proportion of initiator II in the water-soluble monomer solution is 0.1-0.5%.

7. The preparation method according to claim 1, characterized in that: In the steps S1 and S2, the deoxygenation method is independently selected from nitrogen replacement for 20 to 40 minutes; Preferably, the stirring speeds of the reaction I and reaction II are independently selected from 100 to 300 r / min; Preferably, the temperature of reaction I and reaction II is independently selected from 40 to 80° C., and the time of reaction I and reaction II is independently selected from 2 to 6 hours.

8. The coated nano-propeller prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The particle size of the coated nano-adjusting agent is 50 to 150 nm; Preferably, the viscosity of the coated nano-propeller is 2000-5000 mPa·S.

9. Use of the coated nano-displacement agent according to claim 8 in low permeability oil field cores.

10. The use according to claim 9, characterized in that: The coated nano-type displacement agent is dissolved in mineralized water and injected into the core, wherein the mass proportion of the coated nano-type displacement agent in the mineralized water is 0.5% to 1.5%.

Citation Information

Patent Citations

  • Nano profile control and displacement material as well as preparation method and application thereof

    CN116023593A